Dental Alloy Sorting By the Thermoelectric Method - Kikuchi, Masafumi (European Journal of Dentistry, 2010)
Objectives: A nondestructive, rapid, and practical method of dental alloy sorting is desirable. In this study, the hypothesis to be tested is that dental alloys show significantly different and high thermoelectric power values, on the basis of which alloy sorting is possible.Methods: Six silver-colored commercial dental casting alloys are used in this study: two silver alloys, one gold-silver-palladium alloy, one cobalt-chromium alloy, one nickel-chromium alloy, and one titanium alloy. The thermoelectric power of their castings was determined against constantan using a simple apparatus developed in a previous study. Linear least square fitting was applied to the measured thermal-EMF-temperature curve to determine the thermoelectric power for the temperature ranges of 298.303 K (temperature difference Δt = 5 K), 298.308 K (Δt=10 K), 298.313 K (Δt=15 K), and 298.318 K (Δt=20 K). The results were analyzed using one-way ANOVA and by the Scheffefs test at a significance level of α=0.01.Results: When the temperature difference was 10 K or less, the difference in the thermoelectric powers of the alloys was not always statistically significant. However, when the temperature difference was 15 K or more, the thermoelectric powers of the six alloys differed significantly.Conclusions: The results indicated the feasibility of rapid sorting of specific dental alloys by the thermoelectric method, provided a sufficiently large temperature difference is achieved. (Eur J Dent 2010;4:66-70)
Keywords: Dental casting alloy; Alloy sorting; Thermoelectric power; Thermal electromotive force; Thermocouple